Analisis dampak transaksi E-Commerce terhadap penerimaan pajak pertambahan nilai - Efan Elfanso; Laura Monica (Politeknik Ganesha Medan, 2023)
This study aims to determine the impact of e-commerce transactions on Value Added Tax (VAT) revenue which is a source of state revenue and development. This research was conducted using a descriptive qualitative approach with a case study research approach. Data collection methods were carried out by interviews, observation and supported by secondary data from the object of research. The data analysis used in this research is descriptive which is supported by quantitative data. The results of this study Based on e-commerce transaction activities, Indonesia has not been able to collect VAT tax on e-commerce transactions in an ideal amount. This can be seen from the value of e-commerce transactions which have increased significantly in the last five years, but tax revenue for e-commerce transactions is inversely proportional, namely experiencing a significant decline in 2021. The conclusion of this study is that the impact of e-commerce on tax revenue is considered sufficient good because tax revenue has increased but in 2021 it has decreased significantly. This significant decrease was caused by a lack of awareness and understanding of taxation by taxpayers who had not paid taxes optimally each year, e-commerce transactions that were difficult to detect from a business standpoint and socialization that had not been carried out thoroughly.